Exactness of the cordes condition of the Hölder property for the gradient of nondivergent elliptic systems - Kalita, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We give an example of a nondivergent elliptic system showing that the classical Cordes condition of the Hölder property for the gradient of solution of a nondivergent elliptic equation is exact if properly extended onto systems.